Risk assessment of Golani’s round herring (Etrumeus golanii) in the Greek seas (northeastern Mediterranean Sea) - Keramidas, Ioannis; Tsikliras, Athanassios C.; Zenetos, Argyro; Karachle, Paraskevi K. (Frontiers in Marine Science, 2023)
Greek waters are the recipient of several alien species, mainly through natural dispersal following invasion and establishment of non-indigenous species (NIS) in neighboring areas, making their monitoring and mitigating their effects of paramount importance. The European Union legislation framework toward alien species invasions considers risk assessments as the top of the spear for a first assessment of NIS and their potential to become invasive or not. The Union List has already included top priority species, with very few marine species. Golani’s round herring (Etrumeus golanii) is a species of round herrings in the family Dussumieriidae, a Lessepsian migrant and belonging to a group of NIS in the Mediterranean basin that are less studied. Its distribution range is mainly limited in the southeastern Mediterranean Sea, while in the Greek seas, it has not yet been observed in the north Aegean and Ionian seas, probably due to temperature and oceanographical reasons. Its presence in the basin is recorded by commercial fisheries landings in several countries (especially purse-seiners), indicating a potentially positive effect on commercial fisheries. A risk assessment of E. golanii in Greek waters was carried out in this work, based on the Risk Assessment Scheme developed by the GB Non-Native Species Secretariat (GB Non-Native Risk Assessment—GBNNRA). An overall semi-quantitative summary of risk, in terms of likelihood of events and magnitude of impacts, was facilitated for several attributors, including confidence levels for each one. The assessment highlighted a very likely possibility of introduction in the Greek seas from neighboring countries, as well as successful establishments of populations with high confidence levels. A moderate magnitude of impact regarding its further spread was deemed, while a minor one was indicated in terms of native species pressure and a minimal one in terms of economic costs and public health. Overall, E. golanii was not characterized as an invasive alien species (IAS) and local communities could benefit from its presence (commercial fisheries); however, further studies focusing on its reproduction and spawning grounds should be implemented.